2018
DOI: 10.1016/j.ymthe.2018.02.019
|View full text |Cite
|
Sign up to set email alerts
|

Radionuclide Imaging-Guided Chemo-Radioisotope Synergistic Therapy Using a 131I-Labeled Polydopamine Multifunctional Nanocarrier

Abstract: Development of biocompatible nanomaterials with multiple functionalities for combination of radiotherapy and chemotherapy has attracted tremendous attention in cancer treatment. Herein, poly(ethylene glycol) (PEG) modified polydopamine (PDA) nanoparticles were successfully developed as a favorable biocompatible nanoplatform for co-loading antitumor drugs and radionuclides to achieve imaging-guided combined radio-chemotherapy. It is demonstrated that PEGylated PDA nanoparticles can effectively load two differen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
32
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 47 publications
(33 citation statements)
references
References 25 publications
(27 reference statements)
1
32
0
Order By: Relevance
“…Beta minus decay provides therapeutic effects, while gamma emissions are used for SPECT imaging 17,22,23. Therefore, 131 I-labeled molecular probes have been developed for theranostic applications in treatment of various kinds of cancer 2427. Several studies have suggested that 131 I-labeled glioma-targeting ligands such as chlorotoxin, and chlorotoxin-like peptides such as Buthus martensii Karsch chlorotoxin (BmK CT), are potential candidates for targeted SPECT imaging and radionuclide therapy of glioma 2831.…”
Section: Introductionmentioning
confidence: 99%
“…Beta minus decay provides therapeutic effects, while gamma emissions are used for SPECT imaging 17,22,23. Therefore, 131 I-labeled molecular probes have been developed for theranostic applications in treatment of various kinds of cancer 2427. Several studies have suggested that 131 I-labeled glioma-targeting ligands such as chlorotoxin, and chlorotoxin-like peptides such as Buthus martensii Karsch chlorotoxin (BmK CT), are potential candidates for targeted SPECT imaging and radionuclide therapy of glioma 2831.…”
Section: Introductionmentioning
confidence: 99%
“…PDA was synthesized from dopamine hydrochloride according to our previous protocol. 31 Transmission electron microscopy (TEM) showed that PDA nanoparticles presented uniform spherical morphology ( Figure 2 A), while the average diameter was around 200 nm as revealed by dynamic light scattering (DLS; Figure 2 B). In order to improve the biocompatibility of PDA nanoparticles, we functionalized PDA with amino PEG at pH 10.0, and the obtained PDA-PEG NPs showed excellent biocompatibility in different physiological solutions ( Figure 2 C).…”
Section: Resultsmentioning
confidence: 99%
“…Synthesis and characterization of PDA-PEG-DOX nanoparticles PDA was synthesized from dopamine hydrochloride according to our previous protocol [31].…”
Section: Resultsmentioning
confidence: 99%
“…PDA nanoparticles were synthesized according to our published protocols with a little modi cation [31]. In brief, 180 mg of dopamine hydrochloride (Aldrich Chemical) was dissolved in 90 mL of deionized water, and then 760 μL of sodium hydroxide (NaOH, 1 mol L -1 ) was added.…”
Section: Synthesis and Functionalization Of Polydopamine (Pda) Nanopamentioning
confidence: 99%